Continous renal replacement therapy: revisited - Aryanugraha, Teguh; Prasetya, Indra (Universitas Brawijaya, 2025)
Patients in condition of acute kidney injury (AKI) and critically ill often benefit from renal replacement therapy (RRT). Patient with hemodynamically unstable in cardiac intensive care, such as those with congestive heart failure, acute myocardial dysfunction, or excessive hemodilution during cardiac surgery, continuous renal replacement therapy (CRRT) is considered to be the suitable renal replacement therapy modality. This paper discusses indications, techniques, and CRRT in cardiac critical care.